RITUAL PATANITI ( STUDI BUDAYA MASYARAKAT DI JAZIRAH LEIHITU KABUPATEN MALUKU TENGAH) - Mujadid Naya (DIALEKTIKA, 2019)
ABSTRACT Singer study entitled "Ritual Pataniti (Cultural Studies Society in Central Maluku district Leihitu Peninsula. Searching Google Articles How Pola Ritual subject matter Pataniti As Jazirah Leihitu Culture Society in Central Maluku district. Singer Research operates research is qualitative WITH deskretif using a sociological approach, and historical. The informant Of Research Singer is a religious figure, traditional leaders and community that knows the issue studied. Research shows that the singer Ritual Pataniti As Jazirah Leihitu Culture Society in Central Maluku district. Seen ASPECTS From; (1) Process, Form and Perestiwa Ritual Pataniti That Shape And pristiwa Ritual Pataniti ie when ADA Musing OR Gen Yang Yang ADA society menimpah People in the village, (2) .Makna and Culture Pataniti For 'community Jazirah (Morella Villages And Hila) , Was A customs Confidence shown to the spirits Datuk-Datuk Yang ADA since PT WORKS OF HUMAN SON time. Believe kepada Allah and Muhammad, believe kepada kita Also sacred And the spirits of the ancestors lieutenant OR BECAUSE they have magical powers supernatural OR That can be helped 'The community is experiencing a disaster. (3), Ritual Pataniti WITH Values of Islamic teachings. For the ritual 'in society Jazirah The key: NO apart from the teachings of Islam. Lumped Pataniti WITH istighatsah, Which means in the name Calling Someone for review asking for help. ON ia intrinsically allowed for a Muslim, believer, Salih, and has an equalizer with Allah. Keywords: Pataniti, Culture Society Jazirah Leihitu